Empowering single mothers through creative group counselling: An effective intervention to improve mental wellbeing - Rafidah Aga, Mohd Jaladin; Janet Ann, Fernandez; Nur Ain Sumaiyah, Abdullah; Adelina, Asmawi (Fakulti Perubatan dan Sains Kesihatan, UPM, 2020)
Introduction: Single parent families, especially, those headed by single mothers are becoming increasingly common around the world especially in Malaysia. Single mothers generally suffer from poorer mental health, job discrimination, abuse and neglect. Hence, they often experience high anxiety, depression, and stress. This calls for research to empower their mental wellbeing. The present study examined the effectiveness of creative group counselling in increasing self-compassion, and decreasing depression, anxiety and stress among single mothers. Methods: A quasi experimental pre-test post-test design was employed in the study. Research participants consisted of 36 single mothers placed in two experimental and two control groups. The instruments used were Self-Compassion Scale and Depression Anxiety and Stress Scale. A self-compassion module was developed that comprised creative therapeutic activities which was administered to the participants in the experimental groups via a 7-session group counselling programme. Participants in the control groups, on the other hand, took part in guidance activities. Semi structured interviews were also performed to gather feedback on the impact of the creative intervention from three single mothers. Results: Findings revealed that creative group counselling successfully increased the level of self-compassion among single mothers. Additionally, the depression, stress and anxiety scores of single mothers were lower after joining the group counselling programme. Furthermore, three themes emerged from the present study which are i) be kind to oneself; ii) mistakes are part of life; and iii) self-transformation. Conclusion: It is evident that the implementation of creative group counselling improves the mental wellbeing of single mothers.